Fanology: Hand-fans in the prehistory of mobile devices. (September 2019) - Davies, Hugh
In the prehistory of mobile devices, the hand-fan plays a crucial role. Extending well beyond use as an air-conditioning tool, the hand-fan has evolved across centuries and cultures to become a portable screen, a game console, an artistic medium, and an elaborate communication device. Drawing on the scholarly, literary, and art history of hand-fans in North Asian and European contexts, this paper excavates a deep history of hand-fans and connects them to contemporary mobile communication devices. This research develops two key aspects of the hand-fan as a communicative apparatus: first, the fan as an optical image surface to store and transmit information, constituting the earliest portable screen, and second, the fan as a haptic and gestural object from which distinct vernaculars arise. This paper maps a radical new trajectory in how we conceptualise the hand-fan in history and the mobile phone in the present.